"I'm Trying to be as Honest as I Can:" An Interview with James Baldwin (1969). (29th September 2015) - Blint, Rich; Büyüm, Nazar
Abstract : This is the first English language publication of an interview with James Baldwin (1924–87) conducted by Nazar Büyüm in 1969, Istanbul, Turkey. Deemed too long for conventional publication at the time, the interview re-emerged last year and reveals Baldwin's attitudes about his literary antecedents and influences such as Richard Wright, Langston Hughes, and Countee Cullen; his views concerning the "roles" and "duties" of a writer; his assessment of his critics; his analysis of the power and message of the Nation of Islam; his lament about the corpses that are much of the history and fact of American life; an honest examination of the relationship of poor whites to American blacks; an interrogation of the "sickness" that characterizes Americans' commitment to the fiction and mythology of "race, " as well as the perils and seductive nature of American power.